Effect of fermented medicinal plants on growth performance, nutrient digestibility, fecal noxious gas emissions, and diarrhea score in weanling pigs. (26th May 2015) - Zhao, Pinyao; Li, Hanlin; Lei, Yan; Li, Tianshui; Kim, Sunki; Kim, Inho
Abstract: BACKGROUND: Antibiotics used as growth promoters in livestock have been banned in the European Union since 2006. Alternatives of antibiotics have focused on phytogenic plants, such as herbs and medicinal plants. No studies have evaluated the use of fermented medicinal plants (FMP) made up of Gynura procumbens, Rehmannia glutinosa and Scutellaria baicalensis in weanling pigs. Therefore, an experiment was conducted to determine the effects of FMP on growth performance, nutrient digestibility, fecal noxious gas emissions and diarrhea score in weanling pigs. RESULTS: FMP supplementation increased ( P < 0.05) average daily gain, average daily feed intake, gain:feed, apparent total tract digestibility of dry matter, nitrogen and gross energy compared with NC treatment, while a linear effect ( P < 0.05) was observed on those criteria. Ammonia, total mercaptans and hydrogen sulfide concentrations were decreased ( P < 0.05) by the supplementation of FMP compared with NC. Additionally, diarrhea score was lower ( P < 0.05) by FMP addition compared with NC during days 0–7 and days 8–14. CONCLUSION: These results suggested that FMP could be used as an alternative to antibiotics by enhancing growth performance and nutrient digestibility, and decreasing fecal noxious gas emission and early diarrhea score of weanling pigs. © 2015 Society of Chemical Industry